Survey of Academic Service Quality in Primary Schools - Djuanda, Dadan; Sunaengsih, Cucun; Syahid, Aah Ahmad; Amalia, Kaniati; Juneli, Juni Artha (Mimbar Sekolah Dasar, 2024)
Quality academic services provide a conducive and supportive learning environment for all education customers at every level of education, and primary schools are no exception. However, the facts in the field show that there are still complaints from teachers, students, and parents regarding academic services in elementary schools. This study aims to analyze the level of academic service quality in elementary schools in Sumedang Regency, focusing on the five main dimensions of reliability, responsiveness, assurance, empathy, and tangibles. This research is a quantitative study using a survey method involving 50 elementary school teachers. The results showed that the quality of academic services in elementary schools in Sumedang Regency fulfills five dimensions with an average of high quality and has been able to meet the expectations and needs of teachers, resulting in satisfaction and good perceptions in the implementation of effective and efficient academic services even though the dimensions of reliability, empathy, and tangibles still need improvement. This research is expected to contribute to schools’ supporting decision-making and determining solutions in more specific areas to realize quality academic services.